Angiography Versus Hemodynamics to Predict the Natural History of Coronary Stenoses: Fractional Flow Reserve Versus Angiography in Multivessel Evaluation 2 Substudy. Issue 14 (3rd April 2018) - Ciccarelli, Giovanni; Barbato, Emanuele; Toth, Gabor G.; Gahl, Brigitta; Xaplanteris, Panagiotis; Fournier, Stephane; Milkas, Anastasios; Bartunek, Jozef; Vanderheyden, Marc; Pijls, Nico; Tonino, Pim; Fearon, William F.; et al.
Abstract : Background: Among patients with documented stable coronary artery disease and in whom no revascularization was performed, we compared the respective values of angiographic diameter stenosis (DS) and fractional flow reserve (FFR) in predicting natural history. Methods: The present analysis included the 607 patients from the FAME 2 trial (Fractional Flow Reserve Versus Angiography in Multivessel Evaluation 2) in whom no revascularization was performed. FFR varied from 0.20 to 1.00 (average 0.74±0.16), and DS (by quantitative coronary analysis) varied from 8% to 98% (average 53±15). The primary end point, defined as vessel-oriented clinical end point (VOCE) at 2 years, was a composite of prospectively adjudicated cardiac death, vessel-related myocardial infarction, vessel-related urgent, and not urgent revascularization. The stenoses were divided into 4 groups according to FFR and %DS values: positive concordance (FFR⩽0.80; DS≥50%), negative concordance (FFR>0.80; DS<50%), positive mismatch (FFR⩽0.80; DS<50%), and negative mismatch (FFR>0.80; DS≥50%). Results: The rate of VOCE was highest in the positive concordance group (log rank: X 2 =80.96; P =0.001) and lowest in the negative concordance group. The rate of VOCE was higher in the positive mismatch group than in the negative mismatch group (hazard ratio, 0.38; 95% confidence interval, 0.21–0.67; P =0.001). There was no significant difference in VOCE between the positive concordance and positive mismatch groups (FFR⩽0.80; hazard ratio, 0.77; 95% confidence interval, 0.57–1.09; P =0.149) and no significant difference in rate of VOCE between the negative mismatch and negative concordance groups (FFR>0.80; hazard ratio, 1.89; 95% confidence interval, 0.96–3.74; P =0.067). Conclusions: In patients with stable coronary disease, physiology (FFR) is a more important determinant of the natural history of coronary stenoses than anatomy (DS). Clinical Trial Registration: URL:https://clinicaltrials.gov . Unique identifier: NCT01132495. Abstract : Supplemental Digital Content is available in the text.